The KTK test in the assessment of children's motor coordination and its relationship with anthropometry and motor performance: a systematic review (Research, Society and Development, 2022)
Objective: To identify what has been published regarding the use of the KTK test in recent years to assess children's motor coordination, and secondarily analyze the relationship between motor coordination, anthropometry, and performance. Methods: A systematic review was carried out in the PubMed and Scielo databases, using the search strategy (test KTK) AND (motor coordination). Inclusion criteria were articles in English or Portuguese; articles from observational or intervention studies and surveys that were carried out between the years 2015 - 2021. Results: A total of 11,221 children make up the total sample of studies. Anthropometric measurements show an inversely proportional relationship with motor coordination, while performance shows a directly proportional relationship. The population profile demonstrates that some anthropometric factors, advanced age, sports practice and specific temperament characteristics of activity and attention-persistence were the strongest predictors for better motor coordination. Conclusion: Recent literature demonstrates that this test has inversely and directly proportional relationships with anthropometric measurements and performance, respectively.